Analisis Faktor Pelatihan Kerja Terhadap Produktivitas Kerja Karyawan Pada PD Surabaya - Adi Adi (Exchall: Economic Challenge, 2020)
This research aims to find outthe achievement ofemployee productivity in PD. Surabaya, mengetahui if job training affects work productivity,to know how much influence between work productivity and work research both simultaneously and partially. This research uses descriptive verivikative research using survey method. The population in this study was all PD employees. Surabaya. The research samples were selected using cluster sampling area techniques. Data collected with coesioners that have been tested validity and derptive, normality test, multi-cardrity test, heterokodesity test, multiple regression test, simultaneous test, coefficient determination test. Based on the results of data processing, the results of regression analysis in this study is 0.672. Based on the results of data analysis there is a significant influence between the factors of work training there is work productivity, this is evidenced statistic hypothesis test shows a significant value (t) 0.000 less than the specified α (0.05) or seen from the performance of testers and Horejected. Based on the results of the above research, it can be concluded that the factor of job training has a significant impact on the productivity of employees' work in pd. Surabaya Cirebon.